Advanced Headache Therapy Outpatient Strategies - Robbins, Lawrence. (Springer International Publishing : Imprint: Springer, 2015)
This cutting-edge guide covers treating migraine and cluster headaches while providing practical clinical advice on approaching challenging patients of all ages. Unique features include:                 - Extensive clinical pearls not available elsewhere                 - Psychiatric comorbidities are explored in depth                 - Extensive case studies explain how to use the vast array of medications                 - Outpatient headache treatment for all ages                 - Guidelines and blueprints for treating complex headache patients                 - The immune system and headache Authored by a renowned expert on refractory headaches, Advanced Headache Therapy is an invaluable guide for physicians and patients.